Cultural Influence on ERP Implementation : a MENA perspective - Gherbi, Ines (My University, 2025)
Enterprise Resource Planning (ERP) systems are widely adopted by multinational organizations to integrate business processes, yet their implementation success remains inconsistent across cultural contexts. This thesis investigates how national cultural differences influence ERP implementation outcomes in the Middle East and North Africa (MENA) region, with a specific focus on SAP projects. While Critical Success Factors (CSFs) frameworks are frequently used to guide ERP deployment, most existing literature disregards culture or treats it as a peripheral factor. Moreover, these frameworks tend to be predominantly Western-oriented. Drawing on Hofstede’s cultural dimensions, this research explores how cultural values actively impact key CSFs such as top management support, project management, user training, ERP team composition and Business Process Reengineering. It employs a qualitative methodology based on semi-structured interviews with ERP consultants who have implemented SAP in Egypt, Jordan, Morocco, and Saudi Arabia. This study reveals that Hofstede's cultural dimensions translate into specific behavioral patterns that systematically influence Critical Success Factor effectiveness. Four consistent areas of influence emerged: hierarchical decision-making patterns, team dynamics, communication styles, and change resistance behaviors. The findings challenge the assumption that CSFs operate uniformly across cultures, revealing instead that cultural values fundamentally reshape how each success factor must be implemented. This thesis extends ERP theory by positioning culture as a contingent factor that fundamentally shapes CSF effectiveness rather than treating it as a separate element. For practitioners, it offers concrete guidelines for adapting implementation approaches to local cultural contexts in the MENA region.
Keywords: ERP implementation, SAP, National Culture, Critical Success Factors, MENA Region, Behaviours